Pnky Modulates Neural Stem Cell Proliferation and Differentiation Through Activation of Wnt/β-Catenin Signaling Pathway - Wu, Haidong; Huang, Jing; Li, Xiaojing; Song, Yali; Chen, Xuxiang; Guo, Yajie (Organogenesis, 2025)
Neural stem cell (NSC) possess the essential properties of pluripotency and self-renewal, making them promising candidates for the treatment of neurological disorders such as Alzheimer's disease (AD), Parkinson's disease (PD), and spinal cord injuries. While previous studies have identified the long non-coding RNAs (lncRNAs) Pnky as a regulator of NSC differentiation into neurons via RNA splicing, its role in NSC differentiation and proliferation through the Wnt/β-catenin pathway remains unclear. In this study, we investigated the mechanism by which Pnky influences the Wnt/β-catenin pathway to promote NSC differentiation into neurons. Using cck8 assays, western blot analysis, and quantitative polymerase chain reaction (qPCR), we found that Pnky knockdown significantly enhanced NSC proliferation and promoted their differentiation into neurons. Additionally, Pnky knockdown resulted in the downregulation of the neural stem cell marker Nestin and upregulation of the neuronal marker β3-Tubulin, through activation of the β-catenin signaling pathway. Conversely, inhibiting the β-catenin pathway hindered both NSC differentiation and proliferation. These findings suggest that targeting the Pnky-mediated Wnt/β-catenin pathway may offer novel strategies for the treatment, diagnosis, and drug development of central nervous system diseases.